QTL mapping reveals both all-stage and adult-plant resistance to powdery mildew in Chinese elite wheat cultivars - Xu, Xiaoting; Ni, Zhongqiu; Zou, Xinyu; Zhang, Yelun; Tong, Jingyang; Xu, Xiaowan; Dong, Yachao; Han, Bin; Li, Simin; Wang, Desen; Xia, Xianchun; He, Zhonghu; et al. (Plant disease, 2023)
Powdery mildew caused by Blumeria graminis f. sp. tritici (Bgt) is a threat to wheat production in China. Mapping quantitative trait loci (QTL) for resistance to powdery mildew and developing breeder-friendly markers are important initial steps in breeding resistant cultivars. An all-stage resistance gene and several QTL were identified using a population of 254 recombinant inbred lines (RILs) developed from a Jingdong 8/Aikang 58 cross. The population was evaluated for powdery mildew resistance across six field environments over three consecutive growing seasons utilizing two different mixtures of Bgt isolates, named #Bgt-HB and #Bgt-BJ. Using genotypic data obtained from the Wheat TraitBreed 50K SNP array, seven stable QTL were identified on chromosome arms 1DL, 2AL, 2DS, 4DL, 5AL, 6BL.1 and 6BL.2. The QTL on 2AL conferred all-stage resistance to Bgt race E20 in greenhouse tests and explained up to 52% of the phenotypic variance in field trials but was resistant only against #Bgt-HB. The gene involved in this QTL was predicted to be Pm4a based on genome location and gene sequence. QPmja.caas-1DL, QPmja.caas-4DL and QPmja.caas-6BL.1 were identified as potentially new QTL for powdery mildew resistance. QPmja.caas-2DS and QPmja.caas-6BL.1 were effective against both Bgt mixtures indicating their probable broad-spectrum resistance. A Kompetitive Allele-Specific PCR (KASP) marker closely linked to QPmja.caas-2DS was developed and validated in a panel of 286 wheat cultivars. Since both Jingdong 8 and Aikang 58 have been leading cultivars and breeding parents, the QTL and marker reported represent valuable resources for wheat researchers and breeders.